The Impact of Educational Intervention of HighRisk Pregnancy and HighRisk Childbirth on Knowledge, Attitude, and Behavior in Recognizing Danger Signs in Pregnancy: A Single Blind Clinical Trial - JM Seno Adjie; Devi M Malik (Indonesian Journal of Obstetrics and Gynecology, 2017)
Objective: To assess the impact of additional educational interventions given to pregnant women in identifying high-risk pregnancy and high-risk childbirth by measuring changes in knowledge, attitudes and behaviors in the pregnancy and after childbirth. Methods: This study was a single blind clinical trial conducted at obstetrics out-patient clinic of Dr. Cipto Mangunkusumo Hospital, Jakarta. Total sample were 52 responders, for the 26 responders to the control group and 26 responders to the intervention group. The research instrument was a questionnaire form, which include knowledge, attitude and behaviour of a number of 48 questions. Analysis was performed using SPSS 20 with bivariate analysis. Results: We did not found significant differences in a range of age (30.65 ï‚± 29.38 with 1.20 ï‚± 0.75), education (both groups showed a high level of education) and employment for both groups. We found significant differences on knowledge, behaviour (p = 0.001 and = 0.042, respectively) on the first antenatal care compared with after childbirth. Conclusion: The educational intervention gives significant impact in attitude and behaviour. [Indones J Obstet Gynecol 2017; 5-2: 69-72] Keywords: attitude, behaviour, educational intervention, knowledge